Higher Education Leadership Decision Making in Lecturer Governance - Siti Julaiha; Nur Fitriah; Laili Komariyah (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
The purpose of this study was to unfold the management of lecturers at Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda (UINSI Samarinda), and to observe the leader's decision-making in the management of lecturers at UINSI Samarinda. The type of this research is qualitative research using a case study approach. Data collection techniques were done in the form of in-depth interviews, observation, and documentation. The data analysis technique that the researcher used in this study was interactive data analysis by Miles, Huberman, and Saldana from data collection, data condensation, data presentation, and drawing conclusions. The validity of the data was tested with credibility, transferability, and confirmability. The results of this study indicate that the management of lecturers at UINSI Samarinda was directed in several phases. In the planning phase, there are some steps; the analysis of lecturer needs, recruitment, and selection. The next phase is the placement phase; the lecturers are placed dynamically referring to the lecturer’s expertise and the needs of the department. Then, the education and training phase gives an opportunity for the lecturers to continue their studies. In the career development phase, the lecturer's career is in line with his/her educational background and the lecturer's performance. Career development and lecturer performance assessment really depend on the leader’s policy. Lecturer performance assessment is carried out through a policy verified by two assessors and approved by the direct supervisor. The implication of this research is that the strategy or local wisdom which is the best practice of this institution can be used as a model for lecturer management and innovative decision-making by the leader in the human resource development of a university.